Strengthening Our Schools to Promote Resilience and Health Among LGBTQ Youth: Emerging Evidence and Research Priorities from The State of LGBTQ Youth Health and Wellbeing Symposium - Johns, Michelle M. (LGBT Health, 2019)
Lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) adolescents face well-documented health disparities in suicide risk, substance use, and sexual health. These disparities are known to stem, in part, from stigma directed toward LGBTQ youth in the form of minority stressors such as violence, discrimination, and harassment. Given the proportion of time that LGBTQ students spend in school, schools provide a critical context within which protective factors may be developed and leveraged to improve the health and wellbeing of these populations. This article provides a summary of key findings from a discussion among researchers, practitioners, and community members who participated in “The State of LGBTQ Youth Health and Wellbeing: Strengthening Schools and Families to Build Resilience,” a public symposium held in June 2017. We detail emerging science on and future priorities for school-based research with LGBTQ youth which were identified by attendees at this meeting, with a particular focus on intersectionality, supportive adults in schools, and in-school programs. We call for more school-based research on priority gaps such as how LGBTQ students' intersecting identities affect their in-school experiences, how to design professional development programs that cultivate supportive educators, and how to leverage gay–straight alliances/gender and sexuality alliances as sites of health programming for LGBTQ students.